2010
DOI: 10.1007/s00431-009-1137-3
|View full text |Cite
|
Sign up to set email alerts
|

Colistin administration to pediatric and neonatal patients

Abstract: Emergence of multidrug-resistant Gram-negative nosocomial pathogens has led to resurgence of colistin use. Safety and efficacy data regarding colistin use in pediatric patients are sparse, while optimal dosage has not been defined. We present a case series of neonates and children without cystic fibrosis treated with various doses of colistin intravenously. The records of patients who received colistin in a tertiary-care hospital from January 2007 to March 2009 were reviewed. Thirteen patients (median age 5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
79
7
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 40 publications
11
79
7
1
Order By: Relevance
“…A number of studies have been conducted on the systemic use of colistin in adults, mostly in critically ill patients [7][8][9]. However, information on the efficacy and safety of colistin therapy in children is limited [2,6,10]. The aim of this multicentre study was to investigate the efficacy and safety of colistin therapy in the treatment of serious nosocomial infections in paediatric Intensive Care Unit (PICU) patients.…”
Section: Introductionmentioning
confidence: 98%
“…A number of studies have been conducted on the systemic use of colistin in adults, mostly in critically ill patients [7][8][9]. However, information on the efficacy and safety of colistin therapy in children is limited [2,6,10]. The aim of this multicentre study was to investigate the efficacy and safety of colistin therapy in the treatment of serious nosocomial infections in paediatric Intensive Care Unit (PICU) patients.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, there have been several reports of successful treatment of MDR gram-negative bacterial VAP with aerosolized colistin in patients without cystic fibrosis [11,28,35]. Aerosolized delivery may be less toxic than intravenous colistin, but the available data on the safety and efficacy of aerosolized colistin are mostly from adult patients [8,9,23]. Here, we report our experience with aerosolized colistin treatment in two preterm and one term infants with MDR gram-negative bacterial VAP and discuss the new role of this antimicrobial agent in the new era of antibiotics and microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…13 Colistimethate has limited evidence for use in S maltophilia infections. In a recent case series, Iosifidis et al 14 reported their results with use of intravenous colistimethate in several pediatric patients. Two patients had S maltophilia susceptible to colistimethate.…”
Section: Discussionmentioning
confidence: 99%